(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
The prevalence of diabetes worldwide has been increasing steadily in recent years; And the risk of macro and micro vascular complications increases with it, so it is the number one cause of blindness, renal disease, amputations, and others. The presence of hypomagnesemia in millions of diabetic patients may affect the development of these complications. The present study aims to study the relationship between serum magnesium level and the degree of glycemic control in type 2 diabetes patients and to study the prevalence of hypomagnesemia in type 2 diabetes patients, and relationship between serum magnesium level and diabetic retinopathy. The sample included patients with type 2 diabetes who visited the endocrinology clinic at Tishreen University Hospital between December 2019 and December 2020. An intravenous sample was taken for tests of magnesium and fasting blood glucose (FBG), glycosylated hemoglobin (HBA1c), urea, creatinine, HGB, and the rest of the available analyzes. Patients were classified according to their serum magnesium values into either the normal magnesium group or the hypomagnesemia group (<1.7mg/dL). The study sample included 90 patients ranging in age from 32-81 years, 47 of whom were males (52%). The prevalence of hypomagnesemia in the study sample was 25%. The mean of HBA1c values of the hypomagnesemia group were greater than that of the normal magnesium group (10.4±1.75 VS 8.95±1.15, 0.001>P) and the degree of glycemic control(according to HBA1c) was correlated reversibly with the serum magnesium values (r=-0.53,P> 0.001). hypomagnesemia was found to be associated with poor glycemic control and diabetic retinopathy. The prevalence of hypomagnesemia in patients with diabetes is relatively high, which suggests the importance of treating their hypomagnesemia.